Scientific Evidence of a Clash between Das Sollen and Das Sein in the book Who Rules the World by Noam Chomsky - Nur Rohim Yunus (JOURNAL of LEGAL RESEARCH, 2022)
In Who Rules the World?, Chomsky’s target audience and methods differ somewhat from traditional academic treatments of US foreign policy. His analyses are concise but brief vignettes on a relatively broad range of issues relating to American power, including the Israel-Palestine conflict, the threat of nuclear war and relations with Iran. Nonetheless, a handful of common themes thread the essays together, providing answers to the question posed by the title of the book.Perhaps the most provocative theme is Chomsky’s view on the motives behind the exertion of state power at home and abroad. It is often argued that the behaviour of democratic state actors is strongly informed—if not determined—by security considerations; in other words, states’ first priority is to guarantee the protection of the nation and its citizens from external or domestic threats. This, it is assumed, gives state behaviour an aspect of democratic accountability, since citizens have the ability to withdraw their consent for being ruled by a government that cannot make those guarantees. But Chomsky notes that this is unlikely to be the primary motive behind state behaviour, not least because in the American context as well as elsewhere it has been so unsuccessful. For example, since the beginning of the global “war on terror” there has been a sharp increase in the number of terrorist attacks in both the West and the Middle East, thereby making the world a less safe and secure place than it was before. If the United States’ priority was to eradicate terrorism, Chomsky’s argues, there are considerably more effective and rational ways of doing so than the strategies adopted in the wake of 9/11.